United States rules on electronic evidence collected from smartphones and their influence on China - Yiyang Cao (Wolters Kluwer Medknow Publications, 2019)
The popularity and wide use of smartphones have led to an increase in the debate on the procedure relating to their investigation and search. We should not neglect the protection of citizens' privacy concerning the content of their smartphones since they contain so much personal information. In 2014, the United States (US) Supreme Court addressed two cases, Riley v. California and US v. Wurie, which dealt with smartphone searches and the search incident to arrest exception to the warrant requirement. Police must obtain a warrant when they want to search for evidence in the smartphone of a potential suspect. However, there are exceptions to this requirement: emergencies and exigent circumstances; the consent to search exception; and the "plain view" exception. The procedural law of China contains no legal regulations on smartphone searches. Therefore, we should establish the principles of smartphone searches to strike a balance between the protection of citizens' privacy and the punishment of crime. It is helpful for us to learn from the experience of the US and other countries and limit warrantless searches, improve the writ principles and clarify the scope and procedure of smartphone searches. It is also important to establish corresponding procedural sanctioning and supervisory mechanisms.